Root system distribution of irrigated and nonirrigated conilon coffee - Covre, André Monzoli; Partelli, Fábio Luiz; Gontijo, Ivoney; Zucoloto, Moises (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the distribution of the root system of irrigated and nonirrigated conilon coffee (Coffea canephora). Conilon plants of the clonal variety Emcapa 8111, genotype 02, with five years of age, were used. The design was completely randomized in split‑split plots with five replicates. The treatments consisted of: presence and absence of irrigation (plots), 13 distances from the stem (ten in the direction between rows and three of the planting row) and six soil layers (0–60 cm) in the split‑plots. Roots were collected, washed, scanned, and processed by the Safira software to quantify surface area, length, volume, and diameter. Nonirrigated conilon plants showed greater root surface area, length, and volume per soil volume, as well as less discrepant distribution of roots in the soil surface and in depth, in comparison to irrigated plants. The drip irrigation system promotes higher root distribution in irrigated plants, in the area covered by the wet‑bulb irrigation.